Unlocking the secrets of saliva: the promising potential of salivary biomarkers for evaluating crack use - Marques, Sandra Silva; de Oliveira, Taís Maria Cardoso [UNESP]; Zucco, Gabriela Ribeiro [UNESP]; Sabbag, Fernando; Martinho, Herculano Da Silva; Almeida, Janete Dias [UNESP]; De Araújo, Marcelo Ribeiro (Editora Cubo, 2023)
The forthcoming letter will encompass the following highlights: Crack cocaine use involves smoking a highly addictive form of cocaine, which is a significant concern in Brazil, particularly in urban areas. This addiction is linked to various health problems, including cardiovascular issues, sexually transmitted infections (STIs) like AIDS and syphilis, tuberculosis, and a notable increase in mortality, largely due to violent causes. Furthermore, crack cocaine users are particularly vulnerable to dental caries, gingival inflammation, oral mucosa lesions, and xerostomia.
Desvendando os segredos da saliva: o potencial promissor dos biomarcadores salivares para avaliar o uso de crack
Keywords: Biomarkers; Body Fluids; Crack Cocaine; Oral Health; Quality of Life